Pengaruh Lactation Massage terhadap Produksi ASI pada Ibu Nifas Post Sectio Caesaria di Rumah Sakit - Pande Putu Indah Purnamayanthi; Putu Ayu Dina Saraswati; Ni Made Risna Sumawati (Universitas Faletehan, 2025)
Postpartum mothers who have undergone Caesarean section are susceptible to delays in the lactation process. Lactation massage can be performed to overcome the obstacles in breast milk production. This study aims to analyze the effect of lactation massage on increasing breast milk production in postpartum mothers after Caesarean section. This study is a quasi-experimental type using a two-group pre-post test control group design. The samples of this study consisted of 36 respondents at Wisma Prasanthi Hospital who were selected using non-probability purposive sampling technique, a method of selecting respondent samples that match the research problem. Breast milk production was measured using a measuring cup and an observational sheet before and after the intervention was given. The statistical test used to test the hypothesis was the Mann-Whitney test. The results of data analysis obtained a p-value = 0.000 < α (0.05), which can be concluded that there is an effect of lactation massage on breast milk production in postpartum mothers after Caesarean section. The research result may have implication on professional midwifery education and midwifery service.